Pharmacokinetics of ketamine and its major metabolites norketamine, hydroxynorketamine, and dehydronorketamine: a model-based analysis - Kamp, Jasper; Jonkman, Kelly; van Velzen, Monique; Aarts, Leon; Niesters, Marieke; Dahan, Albert; Olofsen, Erik (British journal of anaesthesia : BJA, 2020)
Recent studies show activity of ketamine metabolites, such as hydroxynorketamine, in producing rapid relief of depression-related symptoms and analgesia. To improve our understanding of the pharmacokinetics of ketamine and metabolites norketamine, dehydronorketamine, and hydroxynorketamine, we developed a population pharmacokinetic model of ketamine and metabolites after i.v. administration of racemic ketamine and the S-isomer (esketamine). Pharmacokinetic data were derived from an RCT on the efficacy of sodium nitroprusside (SNP) in reducing the psychotomimetic side-effects of ketamine in human volunteers. Three increasing i.v. doses of esketamine and racemic ketamine were administered to 20 healthy volunteers, and arterial plasma samples were obtained for measurement of ketamine and metabolites. Subjects were randomised to receive esketamine/SNP, esketamine/placebo, racemic ketamine/SNP, and racemic ketamine/placebo on four separate occasions. The time–plasma concentration data of ketamine and metabolites were analysed using a population compartmental model approach. The pharmacokinetics of ketamine and metabolites were adequately described by a seven-compartment model with two ketamine, norketamine, and hydroxynorketamine compartments and one dehydronorketamine compartment with metabolic compartments in-between ketamine and norketamine, and norketamine and dehydronorketamine main compartments. Significant differences were found between S- and R-ketamine enantiomer pharmacokinetics, with up to 50% lower clearances for the R-enantiomers, irrespective of formulation. Whilst SNP had a significant effect on ketamine clearances, simulations showed only minor effects of SNP on total ketamine pharmacokinetics. The model is of adequate quality for use in future pharmacokinetic and pharmacodynamic studies into the efficacy and side-effects of ketamine and metabolites. Dutch Cochrane Center 5359.